Design and Implementation of a Web-Based Online Registration System for HIMATIF Using the Agile Development Method - Arya Dimas Senoaji; Farid Akbar (Ilmu Bersama Center, 2025)
Efficient and well-organized registration processes are essential for supporting the activities and membership management of student organizations. The Information Technology Student Association (HIMATIF) requires a system that can streamline registration, reduce administrative workload, and improve data accuracy. This study focuses on the design and implementation of a web-based online registration system for Himatif using the Agile development method. The system features member registration, data validation, document uploads, activity selection, and administrative dashboards for managing registrant information. The Agile approach, specifically the Scrum framework, was applied to enable iterative development, continuous feedback, and rapid adaptation to changing requirements. The system was developed using PHP with the Laravel framework and MySQL for database management, ensuring secure and scalable performance. Testing results show that the application meets functional requirements, operates reliably across multiple devices, and significantly reduces the time required for registration compared to manual processes. This system enhances operational efficiency, improves data management, and provides a better user experience for both members and administrators.